Philosophy of Climate Science Part II: Modelling Climate Change. Issue 12 (December 2015) - Frigg, Roman; Thompson, Erica; Werndl, Charlotte
Abstract: This is the second of three parts of an introduction to the philosophy of climate science. In this second part about modelling climate change, the topics of climate modelling, confirmation of climate models, the limits of climate projections, uncertainty and finally model ensembles will be discussed.